2019
DOI: 10.1111/jep.13287
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the costs and benefits of stroke rehabilitation in South Africa

Abstract: ObjectiveThis paper explores the economic value of rehabilitation to South Africa, using a costed example of cerebrovascular accident (CVA) (stroke) rehabilitation.DesignWe report an economic modelling approach using a worked cost‐effectiveness to validate the argument for the cost‐saving benefits of stroke rehabilitation.SettingSouth African health care, employing analysis of available secondary data from South African research and government reports.ParticipantsIn line with international trends in stroke epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The growth over time has been significant and relatively linear, i.e., constant, over the 28-year period; nonetheless, rehabilitation represents a very small portion of all HPSSR. This may be concerning given the current high levels of physical rehabilitation needs worldwide (e.g., in 2017, 40% of the world's non-fatal health loss came from conditions amenable to physical rehabilitation [1]), the significant growth in those needs observed across country and condition types [1,61], the evidence for large gaps in the physical rehabilitation supply [6,29], and the growing evidence on the individual, economic, and broader societal benefits associated to the delivery of appropriate physical rehabilitation services [2,[62][63][64][65]. In other words, we have found that the amount of Rehabilitation HPSSR is a disproportionate to the global population's needs for such services.…”
Section: Discussionmentioning
confidence: 99%
“…The growth over time has been significant and relatively linear, i.e., constant, over the 28-year period; nonetheless, rehabilitation represents a very small portion of all HPSSR. This may be concerning given the current high levels of physical rehabilitation needs worldwide (e.g., in 2017, 40% of the world's non-fatal health loss came from conditions amenable to physical rehabilitation [1]), the significant growth in those needs observed across country and condition types [1,61], the evidence for large gaps in the physical rehabilitation supply [6,29], and the growing evidence on the individual, economic, and broader societal benefits associated to the delivery of appropriate physical rehabilitation services [2,[62][63][64][65]. In other words, we have found that the amount of Rehabilitation HPSSR is a disproportionate to the global population's needs for such services.…”
Section: Discussionmentioning
confidence: 99%
“…4 Louw et al further affirm that 'improving capacity across African healthcare settings is essential to ensure best practice health programmes to increase awareness of stroke and its causes, its early identification and acute management, and its rehabilitation'. 36 In general, stroke care services in Africa are not adequately supported by governments, with limited support for either the development or implementation of national stroke policy frameworks, or limited provision and endorsement of evidence-based clinical practice guidelines. 37 Where policy frameworks or practice guidelines are available, the implementation processes may not be well supported by states, 38 which further limits best practice care for people with stroke.…”
Section: Care For People With Strokementioning
confidence: 99%
“… 4 Louw et al further affirm that ‘improving capacity across African healthcare settings is essential to ensure best practice health programmes to increase awareness of stroke and its causes, its early identification and acute management, and its rehabilitation’. 36 …”
Section: Introductionmentioning
confidence: 99%
“…These services include, amongst others, physiotherapy, occupational therapy, speech and language therapy, orthotics and prosthetics and audiology services. In addition to having individual benefits for users, rehabilitation services have also been shown to result in cost savings greater than initial investments [ 2 ]. Moreover, the growing need for rehabilitation services across countries means that providing rehabilitation services will be a key strategy if the health-related Sustainable Development Goals are to be achieved [ 1 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%